Grave and Nave: An Architecture of Cemeteries and Sanctuaries in Rural Ontario - McIlwraith, Thomas; Hummer, Mark (Ontario History, 2005)
Cultural landscapes are architectural creations, which is to say that all mankind’s scratchings on the earth surface have a style as well as a substance. In this essay we explore the design of Christian church sites and burying grounds established throughout rural Ontario and dating from the early nineteenth century. The liturgical significance of having graves and church aisles facing east appears to have been widely understood and appreciated, but applying these rules on the land frequently failed to occur. In a field study of 150 cemeteries and more than 200 church buildings we find that burials hold to the rule of eastness much more than did churches. We discuss possible reasons for this inconsistency in landscape design.